1995
DOI: 10.1016/0035-9203(95)90109-4
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and the IgE response against Ascaris lumbricoides in children from a tropical slum

Abstract: Helminthic infection can stimulate the interleukin-4 (IL-4)-dependent polyclonal synthesis of immunoglobulin E (IgE) in children endemically exposed to these parasites. As such children are also frequently at nutritional risk, in this study we considered the possible influence of malnutrition on serum IL-4 levels and the IgE response in helminthic infection. We evaluated 85 Ascaris-infected children living in an urban slum area of Caracas, Venezuela, and found that the serum levels of IL-4 and total IgE were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 23 publications
0
25
0
1
Order By: Relevance
“…Several factors, such as service improvement and early diagnosis, in addition to HAART introduction, are involved in this scenario (44)(45)(46)(47). Some studies have linked nutritional status to intestinal parasitic infections (14,15,48). Authors have reported that individuals with compromised nutritional status followed by immunosuppression may have larger numbers of intestinal parasites and more severe infections (49).…”
Section: Discussionmentioning
confidence: 99%
“…Several factors, such as service improvement and early diagnosis, in addition to HAART introduction, are involved in this scenario (44)(45)(46)(47). Some studies have linked nutritional status to intestinal parasitic infections (14,15,48). Authors have reported that individuals with compromised nutritional status followed by immunosuppression may have larger numbers of intestinal parasites and more severe infections (49).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IL-4 stimulates the synthesis of IL-6 by B lymphocytes [33]. High levels of serum IL-4 have been found in malnourished children [34], suggesting an increased IL-4 production by T lymphocytes. Such a fact could also contribute to the raised IL-6 bioactivity observed here in the supernatants of PHAstimulated cultures from the nutritionally deficient group.…”
Section: Discussionmentioning
confidence: 99%
“…IgE levels past 1500 IU/ml are the clinical marker of parasitism. Therefore, in addition to nutritional stress (Hagel et al 1995), high parasite load is a condition under which allergen-specific IgE (the culprit of present-day allergies) is shut down (Hagel et al 1995). While this trade-off hypothesis is useful for understanding the absence of allergic sensitization in some contexts, it does not address the question of why the IgE system appears to produce much "unnecessary" morbidity in the modern world.…”
Section: Physiological Trade-offsmentioning
confidence: 98%
“…First, proteinenergy malnutrition often causes very high serum levels of IgE as a result of altered T cell regulation of IgE production (Keusch 1991). Second, poorly nourished individuals are less likely to experience allergic sensitization than are their better nourished counterparts, after controlling for parasitic infestation (Hagel et al 1995) (Figure 2). This suggests that competition over energy causes a relinquishing of allergen-specific IgE activation at lower levels of total IgE production in nutrient-deprived than in other individuals.…”
Section: Composite Causesmentioning
confidence: 99%
See 1 more Smart Citation